Review of Thaumatographa tortricids in Taiwan (Lepidoptera: Tortricidae: Chlidanotinae: Hilarographini) - Heppner, J. B.; Arita, Yutaka; Bae, Yang-Seop (Zootaxa, 2025)
The genus Thaumatographa Walsingham, 1897 (Tortricidae: Chlidanotinae: Hilarographini) of day-flying tortricid moths is reviewed for the island of Taiwan, with four species recorded, two of which are new: Thaumatographa fennchihwu Heppner & Arita sp. nov. and Thaumatographa kentingana Heppner & Bae sp. nov., and one new subspecies of Thaumatographa aurosa Diakonoff & Arita of Japan, as Thaumatographa aurosa taiwana Heppner & Arita subsp. nov. Hilarographa calyx Razowski, 2009 syn. nov. is treated as new synonym of Thaumatographa mesostigmatias Diakonoff, 1977. The few Thaumatographa larvae are known as borers in shoots or roots of tropical Myrsinaceae, Rubiaceae, and Zingiberaceae. The few Thaumatographa larvae are known as borers in shoots or roots of tropical Myrsinaceae, Rubiaceae, and Zingiberaceae.